2013
DOI: 10.3109/01942638.2013.791916
|View full text |Cite
|
Sign up to set email alerts
|

“It's the Participation that Motivates Him”: Physical Activity Experiences of Youth with Cerebral Palsy and Their Parents

Abstract: Youth with cerebral palsy (CP) face significant barriers to participation in physical activity (PA). There is little information available about the nature of these barriers. Seventeen (17) youth and/or their parents participated in focus groups and individual interviews to identify factors that make it easy or hard to be physically active. Four themes emerged across functional levels: environmental and personal factors, limitations related to impairment in body structure and function, the perception that heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
67
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 22 publications
(25 reference statements)
6
67
0
1
Order By: Relevance
“…Thus, therapists should consider whether they are in the position to positivity influence societal views on inclusion and or enhance the child's social-emotional well-being, and social skills plus offer mental health treatments as a way of improving a child or adolescent's participation. (6) In this issue of the journal, we learn from a second study that barriers to participation identified by children include: the built environment accessibility; lack of funding for appropriate inclusion supports; societal attitudes; personal confidence; physical fatigue; and activity-induced pain (Shimmell, Gorter, Jackson, Wright, & Galuppi, 2013). This finding has also been confirmed in a large population study (Forsyth, Colver, Alvanides, Woolley, & Lowe, 2007).…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…Thus, therapists should consider whether they are in the position to positivity influence societal views on inclusion and or enhance the child's social-emotional well-being, and social skills plus offer mental health treatments as a way of improving a child or adolescent's participation. (6) In this issue of the journal, we learn from a second study that barriers to participation identified by children include: the built environment accessibility; lack of funding for appropriate inclusion supports; societal attitudes; personal confidence; physical fatigue; and activity-induced pain (Shimmell, Gorter, Jackson, Wright, & Galuppi, 2013). This finding has also been confirmed in a large population study (Forsyth, Colver, Alvanides, Woolley, & Lowe, 2007).…”
mentioning
confidence: 85%
“…Parents of adolescents unable to communicate their own needs identify: transfers; dental care; and accessibility as high participation priorities (Livingston et al, 2011). Therefore, it is important that therapists seek to understand what participation activities are wanted and valued by children and adolescents themselves (Shimmell et al, 2013).…”
mentioning
confidence: 99%
“…Further analysis of the interviews and additional questionnaires for the parents provided insights about their physical activity behaviour by organising identified facilitators and barriers according to three stages of change (pre-intention, intention and action) [19]. In interviews with children aged 9-21 years with CP with different gross motor function limitations, environmental and personal factors, limitations in body structure and function, the perception that health benefits alone do not motivate children to be physically active, and variation in preferences for the delivery of activity was identified as facilitators and barriers to physical activity [20]. Early exposure to activities, lack of opportunities close to home, competitiveness, family support and peer interest were found to be important factors affecting physical activities for adolescents without disability, aged 13-18 years and living in rural areas [21].…”
Section: Introductionmentioning
confidence: 99%
“…they are able to be social, learn skills, be independent, have fun and reach personal goals (Shimmell et al, 2013). Shimmell et al's (2013) study gathered data mainly from adolescents as well as from parents and provides findings that may resonate with parents of younger children.…”
mentioning
confidence: 99%
“…Shimmell et al's (2013) study gathered data mainly from adolescents as well as from parents and provides findings that may resonate with parents of younger children. Ryan et al (2014) examined changes in child and family outcomes following provision of an adaptive seating system via the use of a standardised outcome measure with 70 parents of children with disabilities whose age ranged from 1 to 17 years.…”
mentioning
confidence: 99%